ANALYZING TRANSFERABLE SKILLS OF VOCATIONAL STUDENTS TO ALIGN WITH INDUSTRY DEMANDS - Sri Rahayu; Danny Meirawan; Muktiarni Muktiarni; Zahra Ghinaya; Zenita Sabitri (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
The rapid development of the world in the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era has led to changes in various sectors, including the education sector. According to the Indonesian Central Statistics Agency (BPS) in August 2022, Vocational High Schools contribute the highest unemployment rate of 9.42% compared to other educational levels. Therefore, this research aims to analyze the level of Transferable Skills, which refers to skills that can be transferred and consistent in continuous learning, among Vocational High School students and their fulfillment of the needs of the working industry. The method used in this research is descriptive quantitative with a survey technique through a cross-sectional approach to gather information. The instruments used in this study consist of questionnaires distributed to vocational high school students in Indonesia who have undergone job training and supervisors in the industry where the students conducted their job training in various regions in Indonesia. The findings of this research indicate that, overall, the vocational high school students have a satisfactory level of Transferable Skills. However, there are still several aspects that need improvement. This research contributes significantly to understanding the level of transferable skills among vocational high school students and the needs of working industry in the VUCA era. The results of this study can serve as a basis for the development of more effective and relevant vocational education programs to prepare students to meet the demands of an increasingly complex and dynamic job market.